Developing writing skills of engineering students - Данилова, С.; Danylova, S. (My University, 2010)
It deals with developing English learners’ writing skills. It focuses on the importance of teaching essay writing at technical higher school which is considered as a tool for developing students’ thinking abilities, improving their organizing skills in writing. It is paid attention to visual graphic organizers in the process of writing and some ideas how to use them in teaching essay writing
Danylova, S. Developing writing skills of engineering students / S. Danylova // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2010. – Вип. 3. – С. 120–122.
Keywords: writing skills; essay structure; a paragraph; graphic organizers; навички писання; структура есе; параграф; графічні органайзери